Tribological properties of electrodeposited Ni–ZrO2 nanocomposite coatings on copperplate of crystallizer. (3rd October 2019) - Geng, Zhe; Liu, Yang; Zhang, Hongjie
ABSTRACT: Electrodeposited Ni–ZrO2 nanocomposite coatings containing ZrO2 nanoparticles with a mass fraction of 1%, 2% and 4% in wt-% separately used for the copperplate of crystallizer in the continuous casting mould were investigated. Their microstructure and hardness were characterized by OM, SEM, XRD and Vickers hardness tests. The tribological properties of Ni–ZrO2 coatings rubbing with 35CrMo steel pins were evaluated by a pin-on-disc tribometer at 280°C. The results show that the ZrO2 nanoparticles with the mass fraction of 2% in the coating have the fine size, high number density and uniform distribution. They could refine the grain of coating and have the dispersion strengthening effect; thus, they could increase the hardness of coating. The wear mechanism of Ni–1%ZrO2 coating is the abrasive wear, adhesive wear and plastic deformation. The wear mechanism of Ni–2%ZrO2 coating is the abrasive wear. The wear mechanism of Ni–4%ZrO2 coating is the abrasive wear and spallation.